Imunologia das interações materno-fetais no diabete e na hiperglicemia gestacional leve - Fagundes, Danny Laura Gomes [UNESP] (2014)
In diabetes there is controversy regarding the balance between proinflammatory and anti-inflammatory cytokines, but there is lacking in the literature studies on the cytokine profile in maternal blood and colostrum of diabetic mothers. This study evaluated the subsets of cells and cytokine profile Th1, Th2 e Th17 of maternal blood, cord blood and colostrum of diabetic mothers and verify the modulation of cytokines on the functional activity of phagocytes. Were evaluated 124 pregnant women that were divided according to their glycemic status: non-diabetic (ND, ND=45), mild gestational hyperglycemia (HGL, N=30), gestational diabetes mellitus (GDM, N=15) and diabetes mellitus type 2 (DM2, N=34). We observed that the percentages of CD3+ CD45RA+ cells was lower in cord blood group DM2. The CD4+ cells were lower in cord blood groups with HGL and DM2. Maternal blood group DM2 exhibited reduced subset of CD45RA+ cells. Subsets of CD45RO+ cells increased in the colostrum of mothers with DM2. The higher percentage of CD4+ cells were observed in maternal blood and colostrum of mothers with DM2. The concentration of cytokines IL2, IL4 and IFN-γ were similar in all groups. The concentration of IL-6 was higher in colostrum when compared to concentrations in maternal and cord blood. Higher concentrations of IL-17 were found in the maternal blood DM2. In relation of the functional activity of phagocytes was observed that the mononuclear cells of colostrum and blood treated or not with cytokines (IFN-γ and TGF-β), independent of blood glucose levels, exhibited similar phagocytic activity for enteropathogenic Escherichia coli (EPEC). In DM2 group, irrespective of the presence of cytokines phagocytes maternal blood showed lower release of intracellular calcium. Phagocytes of the cord blood of the non-diabetic group when treated by TGF-β, showed an increase in the release of intracellular calcium. The cells of colostrum and maternal blood in the ...